Cross-National Distribution of Research Outputs in Accounting: A Bibliometric Analysis - Monica Lin; Ning Li; Robert Sarikas; Arsen Djatej (Journal of Accounting and Taxation, 2022)
This paper presents an empirical study of the cross-national distribution of research in accounting as a distinctive subject of business research using bibliometric methods. Data utilized in this study has been extracted from Scopus and sample nations include all OECD countries and Asian Newly Industrialized Economies (NIEs).  Our analysis confirms a continuous process of convergence in research specialization in accounting between 1996 and 2015. We also find a developing shift in the connection between accounting and other areas of business research.